2013
DOI: 10.4236/ojo.2013.35043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Distractor Application on Both Radial & Ulnar Side and Radial Side Only for Fracture Distal Radius with Ulnar Styloid Fracture

Abstract: Background: Fracture of distal radius with involvement of the ulnar styloid process is a common clinical problem. It can be treated conservatively, usually involving wrist immobilization in plaster cast or surgically. A key method of surgical fixation is external fixation by distractor. Distractor can be applied either only on the radial side or on both ulnar and radial sides. Materials and Methods: A prospective randomized and comparative study of 1 year duration was conducted on 32 patients admitted in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…These results conclude that that PFN procedure was technically difficult compared to DHS procedure which is in line with the studies Jonnes et al and Faisal et al 10,15 In our study average hospital stay was 17.13 days for DHS and 16.86 days for PFN. This was similar to the studies of Bhatti et al 16 There were less delayed complications in the PFN group compared to DHS group in the current study, which was supported by the studies Faisal et al and Bhakat et al 17 DHS treatment involves wide surgical exposure there by involves considerable blood loss. Also, complications such as varus collapse, implant cut-out was commonly associated with it.…”
Section: Resultssupporting
confidence: 82%
“…These results conclude that that PFN procedure was technically difficult compared to DHS procedure which is in line with the studies Jonnes et al and Faisal et al 10,15 In our study average hospital stay was 17.13 days for DHS and 16.86 days for PFN. This was similar to the studies of Bhatti et al 16 There were less delayed complications in the PFN group compared to DHS group in the current study, which was supported by the studies Faisal et al and Bhakat et al 17 DHS treatment involves wide surgical exposure there by involves considerable blood loss. Also, complications such as varus collapse, implant cut-out was commonly associated with it.…”
Section: Resultssupporting
confidence: 82%
“…In their study, Bhakat et al found fewer complications in the PFN group compared to the DHS group. 14 Gupta et al found in a case series of 400 intertrochanteric fracture patients that PFN has a superior functional prognosis with unstable fractures and requires a reduced operation time. 15 The aggregate ratios for non-union and implant failure in PFN were 1.9% and 2.2%, respectively, according to a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%